2020
DOI: 10.1186/s13229-020-00331-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of autistic traits to taste and olfactory processing in anorexia nervosa

Abstract: Background: There is a heightened prevalence of autism in anorexia nervosa (AN) compared to the general population. Autistic people with AN experience a longer illness duration and poorer treatment outcomes. Whether sensory differences in autism could contribute to altered taste and smell as a potential maintaining factor in AN is under-explored. The aim of this study was to explore whether autistic traits are associated with taste and olfaction differences in AN. Methods: The study recruited n = 40 people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…Assessment of sensitivity to sweet taste in patients with AN appears to be especially interesting, explaining why most attention has been paid to this matter in the literature. Despite data indicating that AN is accompanied by sweet taste hypogeusia (higher recognition threshold, filter paper disc method) [ 4 ] (reduced detection, filter paper disc method) [ 14 ] other research [ 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 ] has concluded that this condition does not involve sweet taste perception, which is the same in patients with AN and in people without eating disorders. Therefore, our results corroborate these researchers’ findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Assessment of sensitivity to sweet taste in patients with AN appears to be especially interesting, explaining why most attention has been paid to this matter in the literature. Despite data indicating that AN is accompanied by sweet taste hypogeusia (higher recognition threshold, filter paper disc method) [ 4 ] (reduced detection, filter paper disc method) [ 14 ] other research [ 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 ] has concluded that this condition does not involve sweet taste perception, which is the same in patients with AN and in people without eating disorders. Therefore, our results corroborate these researchers’ findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have demonstrated decreased taste sensitivity in people with AN [ 1 , 2 , 3 , 4 ]. According to others, in patients affected by AN, sensitivity to sweet taste remains unchanged [ 5 , 6 , 7 , 8 , 9 , 10 ]. Taste sensitivity has a significant influence on food intake control, and its evaluation in patients with AN may provide valuable information about disease development and treatment progress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that depression may result or cause gustatory and olfactory dysfunction. TSCs may cause negative emotions in cancer patients, including disappointment, depression, and sadness [ 9 , 10 ]. One previous study analyzed the data obtained from a nationally representative probability sample of 3005 older American adults and reported an association between any depressive symptoms and olfactory dysfunction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%